Transfer of “Nocardia aerocolonigenes” (Shinobu and Kawato 1960) Pridham 1970 into the Genus Saccharothrix Labeda, Testa, Lechevalier, and Lechevalier 1984 as Saccharothrix aerocolonigenes sp. nov. - LABEDA, DAVID P. (International Journal of Systematic and Evolutionary Microbiology, 1986)
I propose that “Nocardia aerocolonigenes” be placed in the genus Saccharothrix as Saccharothrix aerocolonigenes because it exhibits the following chemotaxonomic properties characteristic of this genus: Whole-cell hydrolysates contain the meso isomer of diaminopimelic acid, rhamnose and galactose are the characteristic sugars, and mycotic acids are absent. This species is phenotypically different from the type species of Saccharothrix, Saccharothrix australiensis (strain NRRL 11239), and deoxyribonucleic acid from the type strain of S. aerocolonigenes was determined to be only 10% homologous to deoxyribonucleic acid isolated from S. australiensis NRRL 11239. A description of the species is presented. The type strain is strain NRRL B-3298 (= ISP 5034 = ATCC 23870 = IFO 3837 = Shinobu No. 701).